2014
DOI: 10.3233/jad-132258
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgery and Anesthesia on Post-Operative Cognitive Decline and Alzheimer's Disease Development: Biomarkers and Preventive Strategies

Abstract: Alzheimer's disease (AD) is a major social and clinical burden in the elderly, affecting 5% of people aged over 65 and 20% aged over 80. Despite improved management, a cure has not been found and hence analysis of predisposing factors to identify preventive strategies has become increasingly important. Surgery and anesthesia have been proposed to increase the incidence of post-operative cognitive decline (POCD) and AD. This is hypothesized to be the result of a malignant neuroinflammatory response and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 141 publications
1
49
0
1
Order By: Relevance
“…Dementia is caused by a variety of diseases and injuries, such as Alzheimer's disease (AD), Parkinson's diseases, multiple sclerosis, and stroke [1,2] . Recently, surgery and anesthesia have been proposed to increase the incidence of AD [3,4] . Surgical procedures and administration of anesthesia are associated with a transient or permanent decline in cognitive function, termed postoperative cognitive dysfunction (POCD).…”
Section: Introductionmentioning
confidence: 99%
“…Dementia is caused by a variety of diseases and injuries, such as Alzheimer's disease (AD), Parkinson's diseases, multiple sclerosis, and stroke [1,2] . Recently, surgery and anesthesia have been proposed to increase the incidence of AD [3,4] . Surgical procedures and administration of anesthesia are associated with a transient or permanent decline in cognitive function, termed postoperative cognitive dysfunction (POCD).…”
Section: Introductionmentioning
confidence: 99%
“…The deterioration and impairment of central cholinergic system is not only related to normal aging (33), but also to neurodegenerative diseases such as AD (20). Cholinesterase inhibitors have been shown to improve cognitive function (20). Several clinical studies showed that drugs with anti-cholinergic effects had negative effects on the cognitive function of patients (33)(34)(35).…”
Section: Mechanismsmentioning
confidence: 99%
“…Cholinergic pathway participates in various cognitive processes including short-term memory, learning and attention (33). The deterioration and impairment of central cholinergic system is not only related to normal aging (33), but also to neurodegenerative diseases such as AD (20). Cholinesterase inhibitors have been shown to improve cognitive function (20).…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations